African commitments for agricultural development goals and milestones for Rwanda - Mitik, Lulit; Fofana, Ismaël; Diallo, Mariam Amadou (International Food Policy Research Institute, 2020)
The study developed a results framework to analyze Rwanda’s progress towards selected CAADP/Malabo, SDGs and Agenda 2063 goals. A Computable General Equilibrium model linked to an income distribution Micro-Simulation model were used to identify priority investment areas for accelerated agricultural growth, poverty and inequality reduction. The current investment trend simulated in the baseline scenario would leave Rwanda off-track to meet these objectives. The analysis of alternative agricultural investment scenarios shows that enhancing the role of the private sector in agriculture will be critical in curbing supply side constraints. The government plays a central role by creating an environment and making the sector more attractive to private investors. Developments outside of the agricultural sector and social protection will be critical to further reduce poverty. Productivity remains one of the major challenges but also one of the most effective solutions for accelerated agricultural growth in Rwanda. Agricultural investments should be designed considering the agricultural value-chain.